2022
DOI: 10.3390/cancers14235758
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Denosumab Use in Giant Cell Tumor of Bone: Dose and Duration of Therapy

Abstract: Giant cell tumor of bone (GCTB) is an aggressive non-cancerous bone tumor associated with risks of sarcoma and metastasis. Once malignancy occurs, the prognosis is generally poor. Surgery remains the main treatment for GCTB. Multidisciplinary management is a feasible option for patients wherein surgical resection is not an option or for those with serious surgery-related complications. Denosumab is an anti-nuclear factor kappa B ligand approved for the treatment of postmenopausal women with osteoporosis, bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…Errani et al conducted a similar study that compared GCTB patients who were treated with and without denosumab. They reported that denosumab increased the recurrence rate in patients who underwent intralesional curettage, which could be theoretically attributed to the entrapment of tumor cells inside the newly formed sclerotic areas or unrestrained proliferation of the stromal cell component of GCTB [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Errani et al conducted a similar study that compared GCTB patients who were treated with and without denosumab. They reported that denosumab increased the recurrence rate in patients who underwent intralesional curettage, which could be theoretically attributed to the entrapment of tumor cells inside the newly formed sclerotic areas or unrestrained proliferation of the stromal cell component of GCTB [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…They also noted risk relapse of 25%, an increased ratio of drug toxicity and other adverse events (hypercalcaemia, atypical stress fractures and osteonecrosis of the jaw) after discontinuation of denosumab treatment. Ultrashort-term (less than 3 months) denosumab treatment prior to surgery achieves the therapeutic effect of a conventional course and reduces the risk of local recurrence, as well ( 42 ). Maintenance of a stable disease in patients with unresectable/metastatic GCTB might be possible by administering reduced doses or less frequent administration of denosumab which was proposed by Lipton et al ( 43 ) in case of treating breast cancer.…”
Section: The Efficacy Of Denosumab Treatmentmentioning
confidence: 99%
“…Denosumab được FDA cấp phép năm 2013 sử dụng cho những bệnh nhân bướu đại bào xương không thể phẫu thuật hoặc phẫu thuật sẽ gây ra những tổn hại không thể chấp nhận hoặc bệnh di căn. Nhiều nghiên cứu đã chứng minh lợi ích của sử dụng denosumab trong điều trị bướu đại bào xương [4], [5], [6], [7]. Điều trị denosumab được tìm thấy là có đáp ứng đáng kể trên lâm sàng, hình ảnh học và mô học.…”
Section: Ca Lâm Sàngunclassified
“…Trong hầu hết các nghiên cứu hiện nay, denosumab được chỉ định với liều 120 mg tiêm dưới da vào ngày 1,8,15 và hàng tháng [4], [5], [6], [7]. Thời gian sử dụng là cho đến khi phẫu thuật cắt bướu được thực hiện, hoặc không thấy sự cải thiện trên lâm sàng, hoặc bệnh nhân mong muốn ngưng sử dụng do tác dụng phụ [4].…”
Section: Liều Lượng Và Thời Gian Sử Dụng Denosumabunclassified
See 1 more Smart Citation